Predicting Marital Intimacy Based on Attachment Styles, Early Maladaptive Schemas, and Love Styles in Married Female Students - Afshin, Amin; Pourmehdi Ganji, Fatemeh; Yaghobiyan, Roghayeh (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aimed to predict marital intimacy based on attachment styles, early maladaptive schemas, and love styles among married female students.Method: The research employed a descriptive correlational design and included all married female students enrolled during the second semester of the academic year 2021. Out of these, 300 individuals were selected as the sample group and were studied. Research instruments included the Young Schema Questionnaire - Short Form (YSQ-SF), Hendrick's Love Styles Questionnaire, Collins and Read's Attachment Style Questionnaire (RAAS), and Thompson and Walker's (1983) Marital Intimacy Questionnaire. Descriptive and inferential statistics were used to analyze the data obtained from these instruments. Descriptive statistics included means and standard deviations, while multiple regression was used to examine the research hypotheses.Findings: The regression results indicated that sacrificial love style and the impaired limits schema negatively predict marital intimacy.Conclusions: It can be concluded that the sacrificial love style and the impaired limits schema negatively explain marital intimacy.